2015
DOI: 10.1515/ffp-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of winter conditions on wild ungulates mortality in the Owl Mountains (Poland)

Abstract: Relations between climatic factors during the winter season (n days with frost <0oC and −10oC; n days with snow cover: >1 cm, >10 cm and >30 cm; maximum snow cover during season [cm]) and mortality in free-living ungulates (red deer Cervus elaphus Linnaeus, 1758, roe deer Capreolus capreolus Linnaeus, 1758 and mouflon Ovis aries musimon Linnaeus, 1758) in the Owl Mountains (Lower Silesia – Poland) in years 1998–2010 were investigated. Significant effects of all analysed climatic factors on ungulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Hunting pressure may also influence natural mortality; Eurasian lynx ( Lynx lynx ) increased roe deer predation during the fall hunting season as roe deer increased use of forests to avoid humans (Gehr et al 2018). Comparatively, natural adult ungulate mortality is most common during winter (Dellinger et al 2018) as demonstrated by greater winter mortality among red deer ( C. elaphus ), roe deer, and wild boar (Jedrzejewski et al 1991, Warchalowski et al 2015).…”
mentioning
confidence: 99%
“…Hunting pressure may also influence natural mortality; Eurasian lynx ( Lynx lynx ) increased roe deer predation during the fall hunting season as roe deer increased use of forests to avoid humans (Gehr et al 2018). Comparatively, natural adult ungulate mortality is most common during winter (Dellinger et al 2018) as demonstrated by greater winter mortality among red deer ( C. elaphus ), roe deer, and wild boar (Jedrzejewski et al 1991, Warchalowski et al 2015).…”
mentioning
confidence: 99%